Baring it all: a study on the perceptions of school librarians and guidance counselors on pornography literacy - Estrellado, Dustin Matthew O.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2022)
Pornography has become popular to young people and present a danger to them because some may use it as a source of information. This could end up in misguided decisions that will cause sexual health problems in the future. Pornography literacy presents a promising solution that will increase young people’s awareness about pornography, its elements, its goals, and its representations.

The objectives of the study are: (1) to know the thoughts of selected school librarians and guidance counselors on pornography literacy programs, (2) to describe the factors affecting their views on the inclusion of pornography literacy in sex education, and (3) to gain an understanding how their perceptions shape the possible implementations. The study employed thematic analysis and utilized semi-structured group or individual interviews to describe participants’ views and opinions.

It was discovered that participants see themselves as a guide to the student’s decision making because they are becoming more literate about pornography. School administration, religion, parents/family, educator/facilitators, values, and budget are the perceived factors emerged that may affect the implementation of pornography literacy. Perceived effects of pornography literacy include: (a) opening students’ mind to be critical towards pornography and its related concepts, (b) giving the students protection from its harms, (c) making students more adventurous and curious, (d) making students informed and removing their curiosity towards pornography, and (e) giving students the free will joke about sexual topics learned.

In conclusion, participants are willing to learn about pornography literacy for the sake of their students. It is reasonable to implement pornography literacy, but they still have reservations about it. They emphasized the importance of training educators/facilitators and meticulous research and development of the program. However, the implementation of the program is far from happening because we do not even have a curriculum for the sex education. We should start in ending the sigma surrounding pornography so that the stakeholders can arrive at the same level of understanding.
Thesis
Keywords: Pornography; School librarians -- Philippines -- Obando (Bulacan).; Student counselors -- Philippines -- Obando (Bulacan).